Systemic effects of Subtilase cytotoxin produced by Escherichia coli O113:H21. (1st March 2017) - Seyahian, E. Abril; Oltra, Gisela; Ochoa, Federico; Melendi, Santiago; Hermes, Ricardo; Paton, James C.; Paton, Adrienne W.; Lago, Nestor; Castro Parodi, Mauricio; Damiano, Alicia; Ibarra, Cristina; Zotta, Elsa
Abstract: Subtilase cytotoxin (SubAB) is a member of the AB5 cytotoxin family and is produced by certain strains of Shiga toxigenic Escherichia coli . The toxin is known to be lethal to mice, but the pathological mechanisms that contribute to Uremic Hemolytic Syndrome (HUS) are poorly understood. In this study we show that intraperitoneal injection of a sublethal dose of SubAB in rats triggers a systemic response, with ascitic fluid accumulation, heart hypertrophy and damage to the liver, colon and kidney. SubAB treated rats presented microalbuminuria 20 days post inoculation. At this time we found disruption of the glomerular filtration barrier and alteration of the protein reabsorption mechanisms of the proximal tubule. In the kidney, SubAB also triggered an epithelial to mesenchymal transition (Wuyts et al., 1996). These findings indicate that apart from direct cytotoxic effects on renal tissues, SubAB causes significant damage to the other organs, with potential consequences for HUS pathogenesis. Importance: Uremic Hemolytic Syndrome is an endemic disease in Argentina, with over 400 hundred new cases each year. We have previously described renal effects of Shiga Toxin and its ability to alter renal protein handling. Bearing in mind that Subtilase Cytotoxin is an emerging pathogenic factor, that it is not routinely searched for in patients with HUS, and that to the date its systemic effects have not been fully clarified we decided to study both its systemic effects, and its renal effects to assess whether SubAB could be contributing to pathology seen in children. Highlights: We report novel effects of SubAB cytotoxin in vivo . Rats develop ascites 20 days after SubAB inoculation. SubAB is capable of triggering cardiac hypertrophy. SubAB elicits vacuole formation in the liver. SubAB alters podocytes cytoskeleton and tubular renal protein handling.